Anodic 3D nanostructuring for tailored applications. (7th February 2012) - Moyen, Eric; Santinacci, Lionel; Masson, Laurence; Sahaf, Houda; Macé, Magali; Assaud, Loïc; Hanbücken, Margrit
Electrochemistry can be used to fabricate different three dimensional objects on the nanometre scale. Porous anodic aluminium oxide (AAO) membranes with varying but controlled morphologies are used in several complementary experiments in physics and biology. The present paper gives a description of the membrane fabrication procedure and presents a selection of applications based on the use of the membranes as evaporation masks in crystal growth experiments, as masks in reactive ion etching experiments or as moulds to fabricate arrays of ordered polymer nanopillars. Applications in energy storage are also briefly mentioned. Finally the fabrication of TiO2 nanotubes (TNT) is described. Their anodic formation is very close to that of the AAO membranes and TNTs offer additional perspectives for applications.